PENGENDALIAN KINERJA, PENDEKATAN KOOPERATIF DAN KOLABORATIF DALAM PEMBELAJARAN PKN KELAS 3 DI SDN 033 TANAH GROGOT - Rusni Pasia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Ferformance Control Using Cooperative and Collaborative Approaches in Pancasila Education Learning for Grade III at SDN 033 Tanah Grogot. Performance control using cooperative and collaborative approaches in Pancasila education learning for Grade III at SDN 033 Tanah Grogot still faces challenges. Therefore, the purpose of this study is to examine performance control using cooperative and collaborative approaches in Pancasila education learning for Grade III at SDN 033 Tanah Grogot.This research employs a qualitative method, with respondents consisting of teachers, students, and the school principal. Respondents were selected through purposive sampling based on the research objectives. Snowball sampling was applied through the involvement of participants related to the main respondents.The research procedure began with the researcher developing instruments and performance control tools using cooperative and collaborative approaches in Pancasila education learning. The research was carried out using interview and observation techniques. Data analysis was conducted through preliminary and final conclusions that emerged during the interview process.The research findings revealed that teacher respondents had prepared, implemented, and evaluated performance control using cooperative and collaborative approaches in Pancasila education learning for Grade III at SDN 033 Tanah Grogot. Student respondents had also prepared, engaged in learning activities, and achieved cognitive intelligence outcomes. Meanwhile, the school principal had facilitated the preparation, implementation, and evaluation of performance control using cooperative and collaborative approaches, which led to improvements in the students' multiple intelligences.